The development of portable electrochemical sensors for environmental and clinical analysis - Kava, Alyssa A., author; Henry, Charles S., advisor; Shores, Matthew P., committee member; Sambur, Justin B., committee member; Dandy, David S., committee member (Colorado State University. Libraries, 2020)
The ability to perform chemical and biochemical analysis at the point-of-need (PON) has become increasingly sought. PON sensing is critical in both environmental and clinical monitoring applications to reduce cost and time of analysis and achieve early detection of potentially harmful pollution and health indicators. Electroanalysis is very well suited to PON sensing applications with miniaturized instrumentation available, fast analysis times, high sensitivity, low detection limits and the ability to be interfaced with both conventional and paper-based microfluidics (μPADs). The primary focus of this thesis is to improve electrochemical sensors for PON applications by: 1) reducing the number of liquid handling steps required by the end user, 2) further development of better performing disposable electrode materials and 3) the proper integration of electrodes with disposable microfluidic paper-based devices. The first half of this thesis, Chapter 2 through Chapter 4, focuses on the development of a new functionality in μPADs coupled with high quality boron doped diamond paste electrodes (BDDPESs). The electrochemical PAD (ePAD) is referred to as the Janus-ePAD after the two- faced Greek god. The Janus-ePAD developed in Chapter 2 takes advantage of the ability to store reagents within porous paper matrices. In the Janus-ePAD, reagents were stored in two separate channels connected by a sample inlet to adjust the sample pH and perform multiplexed electrochemical detection at two analytes' optimal pH conditions. Therefore, the device is able to carry out several liquid handling and operator steps in situ, further simplifying electrochemical PON sensing. In Chapter 3, fundamental electrochemical characteristics of the BDDPEs are then studied in order to improve their electroanalytical utility, providing a guide to the use of this new composite electrode material. Then, in Chapter 4, a second generation Janus-ePAD is developed to overcome several problems typically encountered in ePADs, namely, slow flow rates and analysis times and lowered electrochemical detection sensitivities due to the paper-electrode interface. Both of these problems are addressed by developing a multi-layer Janus-ePAD that consists of a wax-patterned paper layer taped to a transparency film layer, generating microfluidic channel in the gap between the two layers. Passive fluid transport is still achieved within the channel gap via capillary action but at much faster flow rates decreasing analysis time by over 20 times compared to a one-layer Janus- ePAD. The paper-electrode interface is removed by placing screen-printed carbon electrodes (SPCEs) on the transparency film layer, providing increased reproducibility and bulk solution sensitivity. The second main focus of this thesis is the development of better performing electrode materials that retain the simplicity and disposability required for on-site electroanalysis. In Chapter 5, this goal is accomplished by the development of a novel SPCE composition using glassy carbon (GC) microparticles as the active electrode component and a conductive commercial ink as the binder component of this composite electrode material. The GC-SPE is then applied to the detection of the toxic heavy metals Cd and Pb using anodic stripping voltammetry (ASV). The use of GC microparticles as opposed to the widely used graphite powders in the bulk SPCE formulation allows for the GC-SPE to sensitively and quantitatively detect Cd and Pb at environmentally relevant levels without the need for any post-fabrication modification which is typically required for graphite based SPCEs. Following the development of the GC-SPE in Chapter 5, in Chapter 6, a systematic study was carried out to understand the relationship between SPCE composition, or carbon particle type, and electrochemical performance with the goal of improving the electrochemical performance of these single-use, mass producible, inexpensive and disposable electrode materials in their native, or unmodified state. Significantly, it was found that SPCE composition can be optimized and tuned to provide electrochemical sensing performance on par with other types of carbon composites historically believed to outperform SPCEs. The work contained within this thesis achieves the goal of developing better performing PON electrochemical sensing motifs while retaining maximum simplicity of fabrication and operation of ePADs and SPCEs. Through automation of liquid handling steps using a paper-based device, further simplification of sensitive multiplexed electrochemical detection was achieved. The fundamental understanding of the electrochemical performance of SPCEs allowed for further applications without extensive post-fabrication modifications which have historically hindered their translation from academic to real-world settings. The work presented herein can be used to guide further development of electrochemical PON sensors for a variety of environmental and clinical applications.